Laboratory evaluation of deranged liver chemistries in pregnancy - Johnson, Kemmian D.; Perisetti, Abhilash; Thandassery, Ragesh; Inamdar, Sumant; Cheryala, Mahesh; Jecmenica, Mladen; Tharian, Benjamin; Goyal, Hemant (Journal of Laboratory and Precision Medicine; Vol 5 (January 2020): Journal of Laboratory and Precision Medicine, 2019)
Liver chemistries (LCs) serve as important noninvasive methods of assessing liver function, hepatocellular injury and cholestasis. In pregnant women, alterations in some LCs occur as a result of the normal physiologic changes of pregnancy. Despite this, majority of LCs including platelets, alanine aminotransferase (ALT), aspartate aminotransferase (AST), bilirubin, gamma-glutamyl transpeptidase (GGT) and lactate dehydrogenase (LDH), remain within normal limits throughout the course of pregnancy. On the contrary, levels of alpha fetoprotein (AFP) and alkaline phosphatase are expected to rise. Similarly, the coagulation system undergoes significant changes, increasing production of clotting factors and reducing native anticoagulants, all which act to induce a prothrombotic state in preparation for the blood loss associated with delivery. It is, therefore, important to distinguish between laboratory changes associated with normal physiological changes and liver diseases in pregnancy. Abnormal LCs occur at an overall rate of 3–5% in pregnant women. Detection of these abnormalities in LC’s may indicate an underlying liver disease or disease process affecting the liver, which can have negative health implications for both the mother and unborn fetus. A classic approach to liver disease in pregnancy includes liver diseases that are unique to pregnant women, pre-existing liver diseases, and those emerging coincidentally during pregnancy. A variety of changes in LC’s are observed in liver disease in pregnancy, each with a unique pattern of derangements. This review summarizes the differential diagnosis and approach consideration for presentation of deranged LCs in pregnant women, while giving special emphasis to laboratory investigations.